Viruses associated with cassava mosaic disease in Senegal and Guinea Conakry - Okao‐Okuja, G.; Legg, James P.; Traoré, L.; Jorge, M.A.B. (Wiley, 2004)
A survey in Senegal and Guinea Conakry established the presence and incidence of cassava mosaic virus disease (CMD) in both countries. CMD occurred in all the fields surveyed, although its incidence was higher in Senegal (83%) than in Guinea (64%). Populations of the whitefly vector, Bemisia tabaci, were low in both countries averaging 1.7 adults per shoot in Guinea and 3.2 in Senegal. Most infections were attributed to the use of infected cuttings, 86 and 83% in Senegal and Guinea, respectively, and there was no evidence of rapid current‐season, whitefly‐borne infection at any of the sampled locations. Disease severity was generally low in the two countries and averaged 2.5 in Guinea and 2.3 in Senegal. No plants with unusually severe CMD symptoms characteristic of the CMD pandemic in East and Central Africa were observed. Restriction fragment length polymorphism (RFLP)‐based diagnostics revealed that African cassava mosaic virus (ACMV) is exclusively associated with CMD in both the countries. Neither East African cassava mosaic virus (EACMV), nor the recombinant Uganda variant (EACMV‐UG2) was detected in any sample. These survey data indicate that CMD could be effectively controlled in both countries by phytosanitation, involving the use of CMD‐free planting material and the removal of diseased plants.